PENGARUH BULLYING TERHADAP KETERAMPILAN SOSIAL ANAK DI LINGKUNGAN SEKOLAH DI SD NEGERI 066050 DI KECAMATAN MEDAN DENAI - Maria Enjel Veronika Sianipar; Rumiris Lumban Gaol; Saut Mahulae; Darinda Sofia Tanjung (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article describes the impact of bullying on students' social skills at SDN 066050 Medan Denai. The type of research study described in this study was quantitative survey research. A quantitative research study method can be defined as a research method based on the philosophy of positivism and used to examine certain populations or samples. The data collection technique used the instruments of the research. The subjects in the study involved the students of SD Negeri 066050 Medan Denai in the academic year of 2020/2021. Based on the results of the research obtained, the result showed that there was an effect of bullying on children's social skills at SD Negeri 066050 Medan Denai. The results of the study on the frequency of the bullying victim category showed that the students with having less bullying category were 29.6%, while the students with having high bullying category were 22.2%. And those who have a percentage in the bullying category frequency are enough at 18.5. Clearly, it could be concluded that the effect of bullying on children's social skills at SD Negeri 066050 Medan Denai with the category of bullying behaviour is low.